Butt or face? : revenge of the butts - Lavelle, Kari (Sourcebooks eXplore, 2024)
"Are you ready for round two of the hilarious guessing game picture book? Discover fascinating facts about animals while guessing if you're looking at a butt or a face! Butt or Face? Volume 2 continues the delightfully cheeky challenge with a whole new set of animals from all over the world. Examine a close-up photo of an animal and then guess whether you're looking at the top or the...um...bottom. The answer is revealed on the next page with a compete photo of the animal! Also included are factual animal details along with how these animals use camouflage or other trickery to engage with their home. Readers will discover animals like the alien butt spider who turns leaves into burrito-like hideaways, the leaf-tailed gecko whose body mimics the leaves and bark of a tree, and many more!"--